Fundraising organisations for Basque children and Spanish refugees - National Joint Committee for Spanish Relief (1940)
1940 038-0040-003 For your Information:- NATIONAL JOINT COMMITTEE Is a fund raising body for the following administrative Committees, Organising Secretary Mrs. V.E. Miller and a small staff of Spaniards. Any funds which you may collect should be addressed to this Committee earmarked, if you wish for special work. Advice will be given on running appeals and entertainments information supplied and literature can be obtained. There is an excellent group of Spanish players who will dance and sing for you at any entertainment which you may organise. BASQUE CHILDREN'S COMMITTEE There are now 470 children in this country who must be supported; all those who can have already returned to Spain, though small repatriation parties still leave at intervals. This Committee is under the care of the Organising Secretary Dr. Camps, and a small staff; she asks for your collaboration in finding further offers of private hospitality mostly for boys between the ages of 10 and 14, and to help with the adoption scheme. (Full particulars of children together with photographs can be supplied where a group of friends "adopt" a Basque boy or girl they can be relieved of all domestic problems in this connection if they will undertake to supply the money for the child, for a definite period.). You can also organise entertainments for the maintenance of a Basque Hostel and appeals generally for the children. BASQUE BOYS TRAINING COMMITTEE Which is a subsidiary of the Basque Children's Committee, was formed in May, 1939, under the Chairmanship of Mr. Robert Willis, Secretary of the London Trades Council, and the Secretary, Miss M. Garrett, to undertake the special responsibility for the older Basque boys in England. A technical department within the Basque Children's Committee, it has aimed to provide every boy with a training in Industry or Agriculture that will enable him in the future to become independent and self-supporting. It has been able to find openings in engineering, tailoring, agriculture, and a number of other trades, for more than 150 boys, and at the present time all the boys of an age to work are in employment under Trade Union conditions. A heavy expense has still to be met, however, in supplementing the wages of a group of 40-50 boys who are only partially self-supporting, and in assisting those who fall temporarily out of work through sickness,short time, or other reasons. They appeal for money to enable them to carry on this work, also for gifts of clothing and shoes (particularly sizes 7-8). BRITISH COMMITTEE FOR REFUGEES FROM SPAIN There are 325 adult Spanish Refugees in England of which 90 are in work and self-supporting. The Organising Secretary of this Committee is Miss Elizabeth Montagu-Pollock, with a small staff mostly Spaniards, doing very varied work. a) Please help find employment. Full details of individual qualifications will always be supplied on request. b) Hospitality is required especially for women with babies, and middle aged men. c) the work of the Perpignan office in France can be helped to carry on its invaluable work of liaison between families here and abroad, refugees can get their papers put in order and get advice. The Committee has done invaluable work in protecting refugees arriving in this country as stowaways. Mens clothes are always needed. 292/946/38/40(III)